Stapled Haemorrhoidectomy Compared with Milligan-Morgan Excision for the Treatment of Prolapsing Haemorrhoids: A Prospective Study - Azhar, Muhammad Usman; Umer, Abdullah; Salman Majeed, Ahmed; Muhammad Hamza; Saeed, Kanwal; Nasir, Ali; Qammar, Bilal (Indus Journal of Bioscience Research, 2024)
Background: Haemorrhoids, a common rectal and anal pathology, present with symptoms such as pain, bleeding, and prolapse caused by oedematous vascular formations in the anal canal. The conventional Milligan-Morgan haemorrhoidectomy (MMH) and stapled haemorrhoidopexy (Stapled Haemorrhoidectomy, PPH) are frequently used surgical techniques for prolapsing haemorrhoids. Aim: To compare Stapled Haemorrhoidectomy and Milligan-Morgan Haemorrhoidectomy in treating prolapsing haemorrhoids. Methodology: This prospective comparative cross-sectional study analyzed early postoperative outcomes in 60 patients undergoing either PPH or MMH. The study was conducted at Jinnah Hospital, Lahore. Data were collected for six months’ duration from January 2024 to June 2024 using a Likert scale questionnaire adapted from Khan et al. (2009). Descriptive statistics summarized continuous variables like operative time, VAS pain scores, and hospital stay, while categorical variables were analyzed using frequency distributions and the Chi-square test to assess associations between complications and procedure type. Findings and Conclusion: Stapled Haemorrhoidectomy showed significant advantages over MMH, including shorter operative time, reduced postoperative pain, and shorter hospital stays. It was also associated with fewer complications such as postoperative bleeding, urinary retention, infection, and anal stenosis. These findings align with previous studies, confirming that Stapled Haemorrhoidectomy offers better recovery and lower complication rates, making it a preferred option in healthcare settings